Structure and hydrogen bonding of mono-protic ionic liquids composed of N-alkylethylenediaminium cations and trifluoromethanesulfonate anion. (September 2021) - Xu, Yu; Hua, Er; Haghani, Abdolhossein
Abstract: The stabilities of some of the possible molecular structures, intermolecular hydrogen bonding interactions, and protonation sites of chelating mono-protic ionic liquids composed of N -alkyl (= Hexyl, Octyl, and 2-Ethylhexyl) ethylenediaminium cations with a trifluoromethanesulfonate anion (TFS), forming [HHex][TFS], [HOct][TFS] and [HEtHex][TFS] were studied using DFT calculations with the M06-2X functional and 6-311G(d, p) basis set. The BSSE-corrected interaction energies (∆ E 0 BSSE ) for the investigated structures range from − 98.3 to − 108.3 kcal mol −1 . NBO and AIM analyses were applied to quantify the relative strengths of the hydrogen bonding interactions and to account for their effect on the stability of various molecular structures. The values of ∆ E 0 BSSE decrease with increasing alkyl chain length and upon introduction of an ethyl branch in the cation. The second-order perturbation energy and electron density indicate that [HAlkyl]1 ＋ [TFS] (protonated at the primary amine, Form A) are more stable than [HAlkyl]2 ＋ [TFS] (protonated at the secondary amine, Form B).